La eliminacion de antecedentes de registros policiales y penales y el derecho a la reinsercion social de las personas privadas de la libertad que hayan cumplido sentencias condenatorias en el Ecuador. - Rúales Benavides, Luis Rolando (2015)
This work of legal research, I made in order to present a legal proposal to the "BACKGROUND REMOVING POLICE AND CRIMINAL RECORDS AND THE RIGHT TO SOCIAL REINTEGRATION OF PERSONS DEPRIVED OF LIBERTY CONVICTIONS WHO TURNED ON THE ECUADOR "to increase a numeral between Section 8 and Section 9 of Art. 230. Chapter One. Talks about the reality of people after completing the sentences have paid their crimes to society in the prisons of our country where they have been allocated for the purpose. This situation is focused on the aspect of reintegration Chapter two discusses the background of the items of the certifications issued by way of personal background, to thereby maintain statistical and accurate data on rates in the country delictogens research. Chapter three discusses the methods used for the development of this legal research, among these the inductive, deductive, analytical, systematic method. Chapter four details the analysis and interpretation of results regarding the research hypothesis through graphs and results from surveys and interviews carried out. Chapter five tells us about the conclusions and recommendations of this research to improve the prison system. Chapter six, we described the proposal which seeks to reform the Art. 230 of the Code of Judicial Function to vindicate the constitutional rights of persons deprived of liberty, who have served a sentence.